Unveiling the hidden dynamics: A configurational analysis of personality traits, demographic factors, and knowledge hiding - Andreas Kallmünzer; Rashid Khurshid; Hafiz Muhammad Usman Khizar; Jingbo Yuan (Journal of Innovation & Knowledge (JIK), 2025)
Knowledge Hiding is a pervasive problem in the workplace, which can have various negative consequences for individuals and organizations. Drawing from the underpinning of complexity theory, this study investigates the complex causal interrelationships associated with knowledge hiding in the workplace. That is, we explore the interrelationships of individual-level factors: i) demographic characteristics (age, gender, education and experience), and ii) personality traits (i.e., Big-5 and the Dark Triad), and knowledge hiding behaviours. We collected data from 157 employees in the hospitality sector and analyzed by using fuzzy-set qualitative comparative analysis (fsQCA). Our results highlighted multiple configurations of the demographic characteristics and personality traits (i.e., causal conditions) leading to knowledge hiding behaviours (i.e., outcome). Our findings revealed a total of 25 unique profiles combining personality traits and demographics factors-14 associated with the presence of knowledge hiding, and 11 linked to its absence. In particular, Machiavellianism emerged as a core condition driving the presence of knowledge hiding, while extraversion was identified as a core condition associated with its absence. This is the first-ever study comprehensively investigating distinct profiles resulting from the interplay between employees' personality traits and demographic factors associated with their knowledge hiding behaviour.
Keywords: M12; M50; 650; Knowledge hiding; Complexity theory; FSQCA; Big-5 personality traits; The dark triad